The Essence of Paying Compensation To Victims of Fair-Based Fraud According To John Rawls - Johan Widjaja; Hartiwiningsih Hartiwiningsih; Erny Herlin Setyorini (Journal Research of Social Science, Economics, and Management, 2024)
This article aims to discuss and analyze the nature of justice-based compensation payments to victims of fraud, the problem approaches used are a conceptual approach, a statutory approach, a comparative approach, a case approach and finally a philosophical approach. This research uses normative research by studying and understanding law as norms or positive legal rules. Sources of legal materials are obtained from legislation, literature books, theory and legal journals. Where later it will be used to find out what the essence of compensation payments should be that provides justice for victims of criminal acts of fraud to obtain their rights, namely through the reconstruction of regulations by adding sanctions in the form of criminal compensation for losses experienced as a result of the criminal act, due to criminal witnesses who were present. This applies only to giving prison sentences without paying attention to the victims.